2015
DOI: 10.1186/s40176-015-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Migration and educational aspirations – Another channel of brain gain?

Abstract: International migration not only enables individuals to earn higher wages but also exposes them to new environments. The norms and values experienced in destination countries can change the behavior of migrants and also of family members left behind. This paper suggests that brain gain can take place due to a change in the educational aspirations of caregivers in migrant households. Estimates for Moldova show that international migration raises parental aspirations in households located at the lower end of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Recently, Böhme (2015) has shown that international Moldovan migrants increase education aspirations at home, and Démurger and Xu (2015) have stressed the importance of education for migrant parents in China. On the other hand, the absence of parents in the household due to migration has been found to lead to reduced investment in children's education in a number of studies.…”
mentioning
confidence: 99%
“…Recently, Böhme (2015) has shown that international Moldovan migrants increase education aspirations at home, and Démurger and Xu (2015) have stressed the importance of education for migrant parents in China. On the other hand, the absence of parents in the household due to migration has been found to lead to reduced investment in children's education in a number of studies.…”
mentioning
confidence: 99%
“…Other reasons such as children's ability or the unavailability of secondary schools make up less than 20% of reported (main) constraints. Panel B shows that the likelihood of reporting barriers also decreases according to our 2SLS regression (see also Böhme 2015). Controlling for all the usual variables, we find that migration significantly decreases the likelihood of the main caregiver reporting barriers to the child's education by about 62 percentage points (average partial effect after an IV probit, see column 4).…”
Section: The Role Of the Income Channelmentioning
confidence: 76%
“…Although it is more costly and difficult to enter the EU labor market, the long-term remuneration is on average higher than for migration to Russia (MPC 2013;World Bank 2014). Böhme (2015) provides evidence that in Moldova migration is associated with higher educational aspirations at the bottom end of the educational distribution and does not affect educational aspirations negatively for any other part of the distribution.…”
Section: The Moldovan Casementioning
confidence: 92%
See 1 more Smart Citation
“…When they return to rural areas, they have an incentive to devote more resources to their children's education (Lee and Park 2011). Böhme (2015) finds that a caregiver's change in educational aspiration can result in "brain gain" of their family members, especially for those located at the lower end of the human capital distribution.…”
Section: How Return Migrant Parents May Affect Children's School Perfmentioning
confidence: 99%